The effect of inoculation with Trichoderma harzianum and Trichoderma viride and Glomus mosseae on same growth parameters of tomato plants (Solanum lycopersicum L.) - Idan, Razzaq Owayez (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted to evaluate the effect of Trichoderma harzianum and Trichoderma viride, and two isolates of Glomus mosseae (G1 and G2) fungi and their combination on the concentration of the tomato foliage system (Solanum lycopersicum L(.The results revealed that all tested bioagents and their combination induced significantly increased all test growth parameters compared to the control treatment. The results also showed that the dual inoculation with Trichoderma harzianum + G1 , Trichoderma harzianum + G2 recorded significant superiority over all tested treatment in the concentration of the macro elements which recorded 480 and 468.33 % for total Nitrogen content 0.483 and 0.400 % for Phosphorus content 4.296 , 4.253 % for Potassium and the micro elements which recorded 19.67 and 17.67 mg/kg, 42.13 and 40.18 mg /kg , 167.67 and 158 and 2235 and 2112.7 in addition to leaf area and chlorophyll concentration that recorded ( 41.36 and mg/kg 30.83 ) cm2 /plant ( 25.65 and 20.5 ) mg/gm respectively Compared to control treatment, which recorded of 308 % total nitrogen, 0.116 % phosphorus total, 2.3 % total potassium, (Fe 1367, 45 Mn, 21.02 Zn and 7 Cu)) mg / kg and 10.86 cm2 / leaf area, 9.03 mg / g Chlorophyll concentration respectively.